2002
DOI: 10.2527/2002.804926x
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of stocker calves backgrounded on sod-seeded winter annuals or hay and grain

Abstract: Economically viable options for retaining ownership of spring-born calves through a winter backgrounding program are somewhat limited in the southeastern United States. Although sod-seeded winter annual forages produce less forage than those same forages planted using conventional tillage practices, sod-seeded winter annual forages have the potential to provide a low-cost, rapid-gain, ecologically and economically viable option for retaining ownership of fall-weaned calves. A study was conducted during the win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…This treatment provided early summer grazing of the oat in the year of establishment and reduced the need to lower the overall stocking rates on the entire pasture. Sod seeding annual cereals into depleted perennial pastures with limited use of glyphosate herbicide rather than cultivation offered another option to provide high-quality forage for grazing and improve land use efficiency (Wilkinson and Stuedemann 1983;Moyer et al 1995;McCartney et al 1999;Coffey et al 2002). However, little research has been done on this concept.…”
Section: Annual Cereals For Pasture Renovationmentioning
confidence: 99%
“…This treatment provided early summer grazing of the oat in the year of establishment and reduced the need to lower the overall stocking rates on the entire pasture. Sod seeding annual cereals into depleted perennial pastures with limited use of glyphosate herbicide rather than cultivation offered another option to provide high-quality forage for grazing and improve land use efficiency (Wilkinson and Stuedemann 1983;Moyer et al 1995;McCartney et al 1999;Coffey et al 2002). However, little research has been done on this concept.…”
Section: Annual Cereals For Pasture Renovationmentioning
confidence: 99%
“…Research at this same location documented the nutritive value of grasses collected from pastures planted to a wheat and ryegrass mixture, similar to the one we used in our experiment, over a 3-year period [14]. These researchers reported [14] that the crude protein concentrations and in vitro digestibility (dry matter basis) averaged 15.4 ± 1.3% and 59.0 ± 9.1% in January, 20.6 ± 1.9% and 78.3 ± 2.5% in March, and 17.9 ± 6.6% and 74.3 ±3.0% in May, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These researchers reported [14] that the crude protein concentrations and in vitro digestibility (dry matter basis) averaged 15.4 ± 1.3% and 59.0 ± 9.1% in January, 20.6 ± 1.9% and 78.3 ± 2.5% in March, and 17.9 ± 6.6% and 74.3 ±3.0% in May, respectively. The hay used in this experiment averaged 12% crude protein and 58% total digestible nutrients (dry matter basis) over the 3-year period and compared to nutritive values reported for winter-annual pasture [14,15], it can be seen why this type of pasture complements warm-season grass hays and has been successfully used as a supplement for gestating beef cows [1-5,16]. Comparison of the nutritive value among cool-season annual grasses and clovers are few, but Lush [15] reported that the crude protein concentrations in pastures planted to a white clover and annual ryegrass mixture was normally 27% greater than monocultures of ryegrass.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that animals keep a relatively consistent body weight during growth. Healthy normal adult female Boer goats have a body weight that ranges from 55 to 90 kg (Coffey et al, 2002). Goats used in this study were 3 weeks after weaning and an increase in weight was expected across all treatments.…”
Section: Discussionmentioning
confidence: 99%